Novel qEEG Biomarker to Distinguish Anti-NMDAR Encephalitis From Other Types of Autoimmune Encephalitis - Mizoguchi, Tomotaka; Hara, Makoto; Hirose, Satoshi; Nakajima, Hideto (Frontiers in Immunology, 2022)
Objective: To establish the diagnostic biomarker of electroencephalogram (EEG) to distinguish between anti-N-methyl-D-aspartate receptor encephalitis (NMDARE) and other types of autoimmune encephalitis (other AEs). Methods: We reviewed the clinical records of 90 patients with acute encephalitis who were treated in our institution between January 2014 and October 2020. We enrolled the patients who fulfilled the diagnostic criteria for possible AE (pAE) defined by Graus et al. (pAE criteria) and then classified into definite NMDARE and other AEs. We investigated the main syndrome and analyzed all admission EEGs using EEG power value (PV). Statistical significance was tested using the Mann–Whitney U test or Fisher’s exact test. Results: Twenty-five patients fulfilled the pAE criteria and were classified into 9 with definite NMDARE (median age: 21 years; 8 women) and 12 with other AEs (median age: 37.5 years; 6 women). Four were eventually excluded. Speech dysfunction (9/9 vs. 4/12, p=0.005), and movement disorders (6/9 vs. 1/12, p=0.016) were more frequent in NMDARE than in other AEs. The PV analyses revealed the novel quantitative EEG (qEEG) index, namely fast slow ratio (FSR) (PV of total beta/PV of total theta + delta). The median FSR (0.139 vs. 0.029, p=0.004) was higher for NMDARE than other AEs, and the receiver operating characteristic curve area of FSR was 0.86 (95% CI 0.70–1.00). A cutoff value of 0.047 yielded a specificity of 0.75 and sensitivity of 1.00. Focusing on patients who did not meet the ‘probable NMDARE criteria’ in Graus 2016 (proNMDARE criteria) (n=10), the pretest probability of NMDAR antibody test was 0.30 (3/10), which increased in patients with a FSR greater than the cutoff (n=5) to 0.60 (3/5). Conclusions: The NMDARE group highlighted speech dysfunction and movement disorders, and a novel qEEG index FSR accurately distinguished the NMDARE patients from other AEs. The FSR is a promising diagnostic marker for NMDARE that indicates the positive results of NMDAR antibodies in patients with AE when combined with the proNMDARE criteria.